Система суб’єктів нагляду та контролю за охороною, захистом, використанням та відтворенням лісів в Україні - Колісніченко, С. Ю.; Kolisnichenko, S. Yu. (Європейські перспективи. - 2024. - № 1. - С. 213-218, 2024)
Узагальнено, що на сьогодні в Україні діє багаторівнева система суб’єктів нагляду та контролю за охороною, захистом, використанням та відтворенням лісів, до якої залучені і вищі державні органи, і центральні органи виконавчої влади, і місцеві органи влади, і громадськість. Відмічено, що така розгалуженість зазначеної системи призводить до появи дублювання повноважень, сприяє бюрократизації та появи корупційних схем, особливо на рівні органів і служб спеціальної компетенції, які безпосередньо і реалізують заходи нагляду та контролю.

It is argued that the system of subjects of supervision and control over the protection, use and reproduction of forests in Ukraine is an integral entity with an internal hierarchical structure, the constituent elements of which are in close relationship with each other and interact to achieve a common goal. However, despite the fact that the specified system represents the unity of a certain set of elements, focused on the achievement of common goals and the implementation of common tasks, each of the subjects that is part of this system and constitutes its structural element has its own legal status, and therefore, certain features of powers, which are one of the key components of this status. It was emphasized that it is most expedient to classify the relevant subjects taking into account their competence. It is emphasized that the grouping of subjects of the researched system in view of their competence makes it possible to look at the nature, scope and scope of those tasks, functions and powers performed by these subjects within the scope of control and supervision of the protection, protection, use and reproduction of forests in Ukraine. It is summarized that today in Ukraine there is a multi-level system of subjects of supervision and control over the protection, protection, use and reproduction of forests, which involves higher state bodies, central executive bodies, local authorities, and the public. However, it was noted that this branching of the mentioned system leads to the emergence of duplication of powers, promotes bureaucratization and the emergence of corruption schemes, especially at the level of bodies and services of special competence, which directly implement supervision and control measures.

Обобщено, что на сегодняшний день в Украине действует многоуровневая система субъектов надзора и контроля за охраной, защитой, использованием и воспроизводством лесов, в которую вовлечены и высшие государственные органы, и центральные органы исполнительной власти, и местные органы власти, и общественность. Отмечено, что такая разветвленность указанной системы приводит к дублированию полномочий, способствует бюрократизации и появлению коррупционных схем, особенно на уровне органов и служб специальной компетенции, непосредственно и реализующих меры надзора и контроля.
Keywords: суб’єкт; нагляд; контроль; охорона, захист, використання та відтворення лісів; ліси; subject; supervision; control; protection, use and reproduction of forests; forests; субъект; надзор; охрана, защита, использование и воспроизводство лесов; леса